Pengaruh Iklim Sekolah dan Self Control terhadap Perilaku Membolos Siswa SMP - Berlian Mayang Indraswari; Najlatun Naqiyah; Ari Khusumadewi; Wiryo Nuryono (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
The study aimed to determine the influence of school climate and self-control on truancy behavior among junior high school students. A quantitative approach with an ex-post facto design. The sampling technique is purposive sampling in three schools in Surabaya City for grades 7 and 8, involving 143 students. Data collection was conducted using questionnaires on school climate (133 items), self-control (29 items), and truancy behavior (45 items). Data analysis was performed using normality, multicollinearity, heteroscedasticity, simple and multiple linear regression tests. The research findings revealed that there was an effect of X1 on Y (t value = |-11.966| > 1.977; sig 0.00 < 0.05) of 50.4%, there was an effect of X2 on Y (t value = |-11.317| > 1.977; sig 0.00 < 0.05) of 47.6%, and there is an effect of X1 and X2 on Y (F value = 99.044 > 3.06; sig 0.001< 0.05) of 58.6%. Descriptive analysis shows that all three variables are in the moderate range, namely X1 72.7%, X2 67.1%, and Y 67.8%. The research results can provide additional data to schools to improve the quality of the school climate and increase self-control through counseling services with the support of various parties. ____________________________________________________________________Penelitian dimaksudkan untuk mengetahui pengaruh iklim sekolah dan self control terhadap perilaku membolos siswa SMP. Pendekatan secara kuantitatif dengan desain ex-post facto. Teknik pengambilan sampel yaitu purposive sampling di tiga sekolah Kota Surabaya kelas 7 dan 8 sebanyak 143 siswa. Pengumpulan data melalui angket iklim sekolah (133 item), self control (29 item), dan perilaku membolos (45 item). Analisis data dengan uji normalitas, multikoleniaritas, heteroskedastsitas, regresi linear sederhana dan berganda. Temuan riset mengungkapkan ada pengaruh X1 terhadap Y (nilai t= |-11,966| > 1,977; sig 0,00 < 0,05) sebesar 50,4%, ada pengaruh X2 terhadap Y (nilai t = |-11,317| > 1,977; sig 0,00 < 0,05) sebesar 47,6%, dan ada pengaruh X1 dan X2 terhadap Y (nilai F = 99,044 > 3,06; sig 0,001< 0,05) sebesar 58,6%. Analisis deskriptif menunjukkan ketiga variabel pada kelompok sedang yaitu X1 72,7%, X2 67,1%, dan Y 67,8%. Hasil riset dapat menambah data kepada pihak sekolah untuk memperbaiki kualitas iklim sekolah dan meningkatkan self control melalui layanan BK dengan dukungan berbagai pihak.